Articulación social de mujeres: respuestas organizativas para un desarrollo urbano en clave feminista. - SAAVEDRA MELÉNDEZ, VALENTINA; ZAGAL EHRENFELD, GEANINA; VILLALOBOS MORALES, MARITZA (Nomadías)
The crisis experienced in Chile in recent years and the violence in the public space have alerted women and feminists about the use of space in the city. This article reviews experiences and strategies of feminist organizations in Chile that work for cities to be thought from a gender perspective, between October 2019 and 2020. The objective is to analyze the role and functioning of social articulation in the construction of cities with a gender perspective. of genre. For which, it delves into four territorial and virtual experiences, their impact, results and call, in the context of the social revolt, confinement and start of the constituent process. The results highlight the role of the horizontal organization and the work of open self-education as the basis for the articulation of women by cities with a gender perspective, accounting for a movement in gestation with potential for change.